Socio-economic variations in tobacco consumption, intention to quit and self-efficacy to quit among male smokers in Thailand and Malaysia: Results from the International Tobacco Control-South-East Asia (ITC-SEA) survey - Mohammad Siahpush (2018)
Aim: To examine the association of socio-economic position (education, income and employment status) with cigarette consumption, intention to quit and self-efficacy to quit among male smokers in Thailand and Malaysia. Design and setting: The data were based on a survey of adult smokers conducted in early 2005 in Thailand and Malaysia as part of the International Tobacco Control-South-East Asia (ITC-SEA) project. Participants: A total of 1846 men in Thailand and 1906 men in Malaysia. Measurement: Participants were asked questions on daily cigarette consumption, intention to quit and self-efficacy to quit in face-to-face interviews. Findings: Analyses were based on multivariate regression models that adjusted for all three socio-economic indicators. In Thailand, higher level of education was associated strongly with not having self-efficacy, associated weakly with having an intention to quit and was not associated with cigarette consumption. Higher income was associated strongly with having self-efficacy, associated weakly with high cigarette consumption and was not associated with having an intention to quit. Being employed was associated strongly with having an intention to quit and was not associated with cigarette consumption or self-efficacy. In Malaysia, higher level of education was not associated with any of the outcomes. Higher income was associated strongly with having self-efficacy, and was not associated with the other outcomes. Being employed was associated moderately with higher cigarette consumption and was not associated with the other outcomes. Conclusion: Socio-economic and cultural conditions, as well as tobacco control policies and tobacco industry activities, shape the determinants of smoking behaviour and beliefs. Existing knowledge from high-income countries about disparities in smoking should not be generalized readily to other countries. © 2008 The Authors.